Pengaruh Media Colour Board terhadap Kemampuan Mengenal Warna Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal VII - Fitria Gia; Sri Wahyuningsi Laiya; Rapi Us Djuko (Institut Nalanda, 2024)
Early Childhood Education Teacher Education, Faculty of Education. Supervisor I: Sri Wahyuningsi Laiya S.Pd, M.Pd, Supervisor II: Dra. Neat Kami Djuko M.Pd. The problem in this research is whether there is an influence of the